2020
DOI: 10.1016/j.idm.2020.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modelling of COVID-19 confirmed cases in Nigeria

Abstract: The coronavirus outbreak is the most notable world crisis since the Second World War. The pandemic that originated from Wuhan, China in late 2019 has affected all the nations of the world and triggered a global economic crisis whose impact will be felt for years to come. This necessitates the need to monitor and predict COVID-19 prevalence for adequate control. The linear regression models are prominent tools in predicting the impact of certain factors on COVID-19 outbreak and taking the necessary measures to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 15 publications
0
50
2
Order By: Relevance
“…We adopted a linear approach assuming strict exogeneity amongst the explanatory variables. A linear approach was outlined by several studies, as the literature shows the variations in COVID-19 cases deaths and cases fits a linear structural model best when regressed against various exogenous variables ( Adekunle et al, 2020 ; Nguimkeu and Tadadjeu, 2021 ; Ogundokun et al, 2020 ; Rath et al, 2020 ; Sardokie and Owusu, 2020 ). The functional relationship is expressed as: where Y iN are the dependent variables related to aggregated COVID-19 cases and deaths for the individual countries (i) for the total number of countries observed in the dataset (N) and X 1 ,X 2 ,.....,X iN are independent exogenous variables for the ith country in the total number of countries (N).…”
Section: Methodsmentioning
confidence: 99%
“…We adopted a linear approach assuming strict exogeneity amongst the explanatory variables. A linear approach was outlined by several studies, as the literature shows the variations in COVID-19 cases deaths and cases fits a linear structural model best when regressed against various exogenous variables ( Adekunle et al, 2020 ; Nguimkeu and Tadadjeu, 2021 ; Ogundokun et al, 2020 ; Rath et al, 2020 ; Sardokie and Owusu, 2020 ). The functional relationship is expressed as: where Y iN are the dependent variables related to aggregated COVID-19 cases and deaths for the individual countries (i) for the total number of countries observed in the dataset (N) and X 1 ,X 2 ,.....,X iN are independent exogenous variables for the ith country in the total number of countries (N).…”
Section: Methodsmentioning
confidence: 99%
“… Zeroual et al, 2020 , Tomar and Gupta, 2020 , Czarnowski et al, 2008 , El Zowalaty and Järhult, 2020 , Shahid et al, 2020 , Hewamalage et al, 2021 , JimĂ©nez et al, 2020 , Kaushik et al, 2020 , BhedadJamshidi et al, 2020 , Ribeiro et al, 2020 , NaudĂ©, 2020 , Arora et al, 2020 , Ribeiro et al, 2020 , Ogundokun et al, 2020 , Alzahrani et al, 2020 , Shastri et al, 2020 , Alakus and Turkoglu, 2020 , Papastefanopoulos et al, 2020 , Chimmula and Zhang, 2020 , Wang et al, 2020 , Wang et al, 2020 , DataGov , Car et al, 2020 .…”
Section: Uncited Referencesmentioning
confidence: 99%
“…This parallels the findings of Clark (2020), which estimated the number of individuals that may be at increased risk of severe COVID-19 illness due to underlying health conditions at 16% and 31% in Africa and Europe, respectively. Through OLS estimation, Ogundokun, et al (2020) found that travelling history and contacts increase the chances of people being infected with COVID-19 by 85% and 88%, respectively in Nigeria. This result suggests the need for the government to ensure that the travel and tour agencies have better precautions and preparations in place before re-opening.…”
Section: Review Of the Empirical Literaturementioning
confidence: 99%